RAPPORTS HOMME/ANIMAL EN PAYS TUPURI: REPRESENTATIONS SOCIALES ET SOCIOLINGUISTIQUES - Jean Paul BALGA (Diversitate si Identitate Culturala in Europa)
Adamawa-Ubangi language spoken in southwestern Chad and north-eastern Cameroon, the tupuri has many speakers. They have a special relationship with animals, including livestock that does most of the dowry in countries tupuri. In this paper, we describe the representations through the relationship of man with the pet, the woman with the beef, the perception of the dog, guardian of the family compound, the boundaries between man and domestic animal, human and wild animal, and wild animal as a spirit protector, witchcraft and second sight.